Nutrition in selected thyroid diseases - Agnieszka Wałejko; Anna Fabian-Danielewska; Katarzyna Korabiusz (Kazimierz Wielki University, 2019)
The most important course in thyroid diseases is pharmacological treatment - thyroid hormone supplementation or inhibition of gland function in case of its hyperactivity. There is more and more evidence for the beneficial effect of a proper diet on the course of the disease and the effectiveness of the therapy. There are also a lot of scientifically unjustified myths functioning in society, mistakenly imposing too restrictive approaches to people's diet. Nutrition in thyroid diseases should be individualized and adapted to the needs and preferences of a particular patient. Great attention should be paid to the caloric content of meals and the content of micronutrients, especially iodine. A properly developed diet can significantly improve the course of the disease and the quality of life of patients. There is no justification for introducing a gluten-free or lactose-free diet in all cases of Hashimoto's disease.